2017
DOI: 10.1097/md.0000000000006816
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of psychological stress and physical work on blood lipid profiles?

Abstract: Blood lipids disorders are prevalent in the world. Some of their risk factors are modifiable such as mental and physical stress which existed in some places such as work environment.Objective of this study was to determine the effects of psychological and physical stress on the lipid profiles. It was a historical cohort study. The people who were employed as general worker were participated. The study was conducted with flexible interview for getting history, lipid profile examination, and a checklist includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…In woman, we found a mild but significant relation of TG and VLDL with CSD consumption; however, the increase in these metabolic measures has been related with atherosclerotic cardiovascular disease (ASCVD) in epidemiologic and genetic studies [57] and with stress in one experimental study [58], which is congruent with recent findings from our group (in preparation), indicating that woman, and not men, showed a significantly higher perceived stress associated with CSD consumption. This possible association suggests that men and woman may have different stress coping strategies and that the impact of CSD consumption in their metabolism is expressed differently.…”
Section: Discussionsupporting
confidence: 90%
“…In woman, we found a mild but significant relation of TG and VLDL with CSD consumption; however, the increase in these metabolic measures has been related with atherosclerotic cardiovascular disease (ASCVD) in epidemiologic and genetic studies [57] and with stress in one experimental study [58], which is congruent with recent findings from our group (in preparation), indicating that woman, and not men, showed a significantly higher perceived stress associated with CSD consumption. This possible association suggests that men and woman may have different stress coping strategies and that the impact of CSD consumption in their metabolism is expressed differently.…”
Section: Discussionsupporting
confidence: 90%
“…However, low HDL level was observed in all women, regardless of their residency. Again, bad meal composition low physical activity in urban and possibly stress seemed to result in this association, as shown in other studies [42][43][44].…”
Section: Discussionsupporting
confidence: 78%
“…It has been well documented that control of lifestyle variables has a positive impact on lipid profile, and stress is considered a key risk factor for several lipid disorders 39,42. In the present study, some improvements were observed in lipid-profile components in the intervention group compared to controls but these changes were not statistically significant.…”
Section: Discussioncontrasting
confidence: 66%